Development of Analytical Information System for Environmental Monitoring and Observation of Agricultural Cultures - Elena V. BUTSENKO; Aleksandr V. KURDYUMOV (Communications of International Proceedings, 2021)
The processes of change, adaptation and improvement of various economic mechanisms taking place all over the world require economic entities to create new tools that allow these entities to reach a new level of interaction. The article discusses the issue of designing a computer software system for collecting and analyzing data on the environment and the cultivation of agricultural crops. The system under consideration is designed to solve automation problems in agriculture. The purpose of the work is to describe the main processes of developing an information and analytical monitoring system. It allows you to enter the initial information about all the main environmental indicators affecting the cultivation of crops. The selection of data and their grouping is carried out in accordance with the locality of cultivation and harvesting. The system uses several directories for convenient interaction with information, for example, a directory of area maps. The processed data is presented in the form of SQL queries and summary reports. The article describes in detail the programming methods used, data processing algorithms and examples of requests for information selection. Further directions of the development of this topic can be associated with the development of software tools that allow automating various tasks of agronomy using artificial intelligence technologies based on the construction of decision trees, neural networks, the method of fuzzy logic, etc.
Keywords: Information and Analytical System; Automated System; Monitoring; Software; Agriculture; Agricultural Technologies.